Composite electrolyte membrane and preparation method and application thereof
By using the combination of oxide electrolyte, polyethylene oxide, polyether polyurethane, lithium salt and plasticizer in the composite electrolyte membrane, and using a dry preparation method, the problem of difficulty in simultaneously improving the electrolyte content and mechanical properties in the prior art is solved, and efficient electrical conductivity and mechanical properties are achieved.
Patent Information
- Application Number
- CN202311003230.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-25
AI Technical Summary
The existing composite electrolyte membranes require the use of a wet method with solvents involved in the preparation process, and it is difficult to simultaneously improve the electrolyte content and mechanical properties.
The composite electrolyte membrane is prepared by dry preparation method using a combination of oxide electrolyte, polyethylene oxide, polyether polyurethane, lithium salt and plasticizer, and the oxide electrolyte accounts for more than 50% of the total weight.
It achieves high ionic conductivity while improving mechanical strength, flexibility and ductility. It has a simple process and high efficiency, making it suitable for continuous production.
Smart Images

Figure CN119518072A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite electrolyte membrane and a preparation method thereof, as well as application in lithium ion batteries. Background Art
[0002] The diaphragm materials used in lithium-ion batteries generally include inorganic solid electrolytes (such as ceramics and glass), polymer electrolytes, and polymer-ceramic composite electrolytes. Composite electrolyte membranes are generally prepared by a wet process, and the steps for preparing wet electrolyte membranes may include, for example: 1) using an organic solvent to dissolve a polymer electrolyte to obtain a polymer solution; 2) adding ceramic electrolyte powder to the polymer solution and stirring well to obtain an electrolyte slurry; 3) casting the obtained electrolyte slurry on a substrate and drying to obtain a composite electrolyte membrane.
[0003] However, existing composite electrolyte membranes usually require a wet preparation method involving solvents, and it is difficult to obtain both a higher electrolyte content and good mechanical properties at the same time. Summary of the invention
[0004] In response to the above technical problems, the present invention provides a composite electrolyte membrane, which comprises an oxide electrolyte, polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer; wherein the oxide electrolyte accounts for more than 50% relative to the total weight of the composite electrolyte membrane.
[0005] In some specific embodiments, relative to the total weight of the composite electrolyte membrane, the oxide electrolyte accounts for 60-90%, the polyethylene oxide accounts for 1-10%, the polyether polyurethane accounts for 1-10%, the lithium salt accounts for 1-15%, and the plasticizer accounts for 1-15%.
[0006] In some specific embodiments, the oxide electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP).
[0007] In some specific embodiments, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).
[0008] In some specific embodiments, the plasticizer is one or more of succinonitrile, polyethylene glycol, and dioctyl phthalate.
[0009] In some specific embodiments, the weight ratio of the polyethylene oxide to the polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.2.
[0010] In some specific embodiments, the composite electrolyte membrane is prepared by a dry process.
[0011] A second aspect of the present invention provides a method for preparing a solid electrolyte membrane, the method comprising the following steps:
[0012] (1) mixing an oxide electrolyte with polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer to obtain a material mixture;
[0013] (2) forming the material mixture to obtain a solid electrolyte membrane;
[0014] Wherein, relative to the total weight of the material mixture, the oxide electrolyte accounts for more than 50%.
[0015] In some specific embodiments, relative to the total weight of the material mixture, the oxide electrolyte accounts for 60-90%, the polyethylene oxide accounts for 1-10%, the polyether polyurethane accounts for 1-10%, the lithium salt accounts for 1-15%, and the plasticizer accounts for 1-15%.
[0016] In some embodiments, the feed mixture does not contain a solvent.
[0017] In some specific embodiments, the oxide electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP).
[0018] In some specific embodiments, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB).
[0019] In some specific embodiments, the plasticizer is one or more of succinonitrile, polyethylene glycol, and dioctyl phthalate.
[0020] In some specific embodiments, the weight ratio of the polyethylene oxide to the polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.2.
[0021] In some specific embodiments, in step (1), the mixing is performed by grinding, and preferably the grinding time is more than 10 minutes.
[0022] In some specific embodiments, in step (2), the molding is performed by pressure molding, and the molding temperature is preferably 60-80°C.
[0023] In some specific embodiments, in step (2), before the molding, the material mixture is subjected to one or more of the following treatments: fiberization, melting, and softening.
[0024] The third aspect of the present invention provides the use of the composite electrolyte membrane of the first aspect of the present invention or the composite electrolyte membrane prepared by the preparation method of the second aspect of the present invention in a lithium ion battery.
[0025] Advantageous Effects of the Invention
[0026] The present invention creatively combines polyethylene oxide and polyether polyurethane for the preparation of a composite electrolyte membrane, thereby achieving a high content of oxide electrolyte addition. The composite electrolyte membrane thus prepared has very high ionic conductivity while also having high mechanical strength, flexibility and ductility.
[0027] In the composite electrolyte membrane of the present invention, by mixing polyether polyurethane and polyethylene oxide, a mixed ion transport path can be provided to promote Li + The transition from single-chain transmission to three-dimensional transmission in a three-dimensional network greatly improves the ionic conductivity of the electrolyte membrane. In addition, the spring-like properties of the soft and hard segments in the polyether polyurethane molecular chain greatly improve the mechanical strength and flexibility of the electrolyte membrane. Polyethylene oxide has a large adhesive force, and polyether polyurethane is both rigid and flexible, making up for the defects of polyethylene oxide such as low strength and insufficient toughness. As a result, the composite electrolyte membrane can be given the above-mentioned good properties at the same time.
[0028] Furthermore, the composite electrolyte membrane of the present invention is preferably prepared by a dry membrane preparation process, in which no solvent is used, the process is simple, the efficiency is high, and continuous production is possible. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of the composite electrolyte membrane structure of the present invention is shown. DETAILED DESCRIPTION
[0030] The present invention is further described below by means of specific embodiments. Unless otherwise specified, the academic terms used herein have the same meanings as those generally understood by those of ordinary skill in the art.
[0031] The numerical limits or ranges stated herein are inclusive and specifically include all values and sub-ranges within the numerical limits or ranges. In the present invention, "%" means "% by weight" unless otherwise specified.
[0032] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0033] A first aspect of the present invention provides a composite electrolyte membrane, which comprises an oxide electrolyte, polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer; wherein the oxide electrolyte accounts for more than 50% relative to the total weight of the composite electrolyte membrane.
[0034] The structural schematic diagram of the composite electrolyte membrane of the present invention is as follows Figure 1 As shown, the gray large and small balls represent oxide electrolyte particles; the combination of thin solid curved line segments and thick straight line segments represents polyether polyurethane molecular chains, wherein the thick straight line segments are hard segments and the thin curved line segments are soft segments; the dotted curved line segments represent polyethylene oxide molecular chains.
[0035] In the present invention, the oxide electrolyte may be any oxide electrolyte commonly used in lithium ion batteries, such as a ceramic oxide electrolyte. As the oxide electrolyte, for example, it may be selected from lithium lanthanum zirconium oxide (LLZO, i.e., Li7La3Zr2O 12 ), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanate oxide (LLTO), lithium aluminum germanium phosphate (LAGP). Furthermore, the oxide electrolyte may also contain one or more doping elements selected from aluminum, gallium, and tantalum. According to some specific embodiments of the present invention, the oxide electrolyte may be aluminum-doped lithium lanthanum zirconium oxide (LALZO, such as Li (7-x) Al (x) LqCy (2-x) O 12 , where x can be 0.01-0.8).
[0036] The oxide electrolyte is preferably added in the form of powder, and the number average particle size of the oxide electrolyte is preferably 0.5-5 μm, preferably 0.8-2 μm.
[0037] According to a preferred embodiment of the present invention, the ionic conductivity of the composite electrolyte membrane is 2*10 -4 S / cm or more, preferably 3*10 -4S / cm or more.
[0038] According to a preferred embodiment of the present invention, the oxide electrolyte accounts for 60-90%, preferably 80-90%, relative to the total weight of the composite electrolyte membrane. In addition, the oxide electrolyte accounts for, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90% of the total weight of the composite electrolyte membrane.
[0039] In the present invention, the polyethylene oxide used preferably has a number average molecular weight of 500,000 to 1,000,000, preferably 500,000 to 800,000, for example 600,000. According to a preferred embodiment of the present invention, the polyethylene oxide accounts for 1-10%, preferably 2-5%, relative to the total weight of the composite electrolyte membrane. In addition, the polyethylene oxide accounts for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% of the total weight of the composite electrolyte membrane.
[0040] In the present invention, the -COC- in the polyether structure of the polyether polyurethane has a complex Li + The ability of PEO polymer electrolyte to conduct Li + , precisely because of the presence of -COC- functional groups in its long chain. Polyether polyurethane elastomers are composed of hard segments generated by the reaction of diisocyanates with small molecule diols and soft segments generated by the reaction of diisocyanates with long chain polyether polyols. The -COC- functional groups in the soft segments participate in Li + The hard segment acts as a physical cross-linking point to enhance the mechanical strength of the polymer. Thanks to the spring-like properties of the molecular chain, the polyether polyurethane has high mechanical strength and high elasticity. According to a preferred embodiment of the present invention, the polyether polyurethane accounts for 1-10%, preferably 2-5%, relative to the total weight of the composite electrolyte membrane. In addition, in the total weight of the composite electrolyte membrane, the polyether polyurethane may account for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.
[0041] In the present invention, the lithium salt may be any lithium salt commonly used in lithium ion batteries, for example, it may be selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB), wherein lithium bis(trifluoromethanesulfonyl)imide is preferred. According to a preferred embodiment of the present invention, the lithium salt accounts for 1-15% of the total weight of the composite electrolyte membrane, preferably 5-8%. In addition, the lithium salt may account for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% of the total weight of the composite electrolyte membrane.
[0042] In the present invention, the plasticizer can use any plasticizer commonly used in lithium ion batteries, for example, it can be one or more of succinonitrile (SN), polyethylene glycol, dioctyl phthalate, wherein succinonitrile is preferred. According to a preferred embodiment of the present invention, relative to the total weight of the composite electrolyte membrane, the plasticizer accounts for 1-15%, preferably 6-10%. In addition, in the total weight of the composite electrolyte membrane, the plasticizer accounts for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0043] According to some preferred embodiments of the present invention, the weight ratio of polyethylene oxide to polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.2. By adopting the above-mentioned weight ratio of polyethylene oxide to polyether polyurethane, a composite electrolyte membrane with better ionic conductivity, tensile strength and elongation can be obtained. In addition, in the total weight of the composite electrolyte membrane, the weight ratio of polyethylene oxide to polyether polyurethane can be, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.20, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.30, 1:0.31, 1:0.32, 1:0.33, 1:0.34, 1:0.35
[0044] 1. 1:1.1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2, etc.
[0045] According to the present invention, the ionic conductivity of the composite electrolyte membrane can reach 2*10 -4 S / cm or more, preferably 3*10 - 4 S / cm or more, 4*10 -4 S / cm or above or 5*10 -4S / cm or more. Specifically, the ionic conductivity of the composite electrolyte membrane can be, for example, 2*10 -4 Up to 6*10 -4 S / cm.
[0046] According to the present invention, the tensile strength of the composite electrolyte membrane may be greater than 2 MPa, for example, 2-7 MPa; in addition, the elongation may be greater than 5%, for example, 5-25%.
[0047] According to the present invention, in order to further improve the performance of the composite electrolyte membrane, the composite electrolyte membrane is preferably prepared by a dry process, that is, no solvent is used in the preparation of the composite electrolyte membrane.
[0048] A second aspect of the present invention provides a method for preparing a solid electrolyte membrane, the method comprising the following steps:
[0049] (1) mixing an oxide electrolyte with polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer to obtain a material mixture;
[0050] (2) forming the material mixture to obtain a solid electrolyte membrane;
[0051] Wherein, relative to the total weight of the material mixture, the oxide electrolyte accounts for more than 50%.
[0052] In the present invention, the oxide electrolyte can use any oxide electrolyte commonly used in lithium ion batteries, such as a ceramic oxide electrolyte. As the oxide electrolyte, it can be one or more selected from lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP). Furthermore, the oxide electrolyte may also contain one or more doping elements selected from aluminum, gallium, and tantalum. According to some specific embodiments of the present invention, the oxide electrolyte may be aluminum-doped lithium lanthanum zirconium oxide (LALZO). According to a preferred embodiment of the present invention, the oxide electrolyte accounts for 60-90% relative to the total weight of the material mixture, preferably 80-90%. In addition, in the total weight of the material mixture, the oxide electrolyte may account for, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.
[0053] In the present invention, the polyethylene oxide used preferably has a number average molecular weight of 500,000 to 1,000,000, more preferably 500,000 to 800,000, for example 600,000. According to a preferred embodiment of the present invention, the polyethylene oxide accounts for 1-10%, preferably 2-5%, relative to the total weight of the material mixture. In addition, the polyethylene oxide accounts for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% of the total weight of the material mixture.
[0054] In the present invention, the -COC- in the polyether structure of the polyether polyurethane has a complex Li + The ability of PEO polymer electrolyte to conduct Li + , precisely because of the presence of -COC- functional groups in its long chain. Polyether polyurethane elastomers are composed of hard segments generated by the reaction of diisocyanates with small molecule diols and soft segments generated by the reaction of diisocyanates with long chain polyether polyols. The -COC- functional groups in the soft segments participate in Li + The hard segment acts as a physical cross-linking point to enhance the mechanical strength of the polymer. Thanks to the spring-like properties of the molecular chain, the polyether polyurethane has high mechanical strength and high elasticity. According to a preferred embodiment of the present invention, the polyether polyurethane accounts for 1-10%, preferably 2-5%, relative to the total weight of the composite electrolyte membrane. In addition, in the total weight of the material mixture, the polyether polyurethane accounts for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.
[0055] In the present invention, the lithium salt can use any lithium salt commonly used in lithium ion batteries, for example, it can be selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), preferably lithium bis(trifluoromethanesulfonyl)imide. According to a preferred embodiment of the present invention, the lithium salt accounts for 1-15% of the total weight of the material mixture, preferably 5-8%. In addition, the lithium salt may account for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% of the total weight of the material mixture.
[0056] In the present invention, the plasticizer can use any plasticizer commonly used in lithium ion batteries, for example, it can be one or more of succinonitrile (SN), polyethylene glycol, dioctyl phthalate, wherein succinonitrile is preferred. According to a preferred embodiment of the present invention, relative to the total weight of the material mixture, the plasticizer accounts for 1-15%, preferably 6-10%. In addition, in the total weight of the material mixture, the plasticizer accounts for, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0057] According to some preferred embodiments of the present invention, the weight ratio of polyethylene oxide to polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.2. By adopting the above-mentioned weight ratio of polyethylene oxide to polyether polyurethane, a composite electrolyte membrane with better ionic conductivity, tensile strength and elongation can be obtained. In addition, in the total weight of the composite electrolyte membrane, the weight ratio of polyethylene oxide to polyether polyurethane can be, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2, etc.
[0058] In step (1), the mixing is performed so that the material mixture is uniformly mixed, and any mixing method in the prior art can be used. In order to fully mix the above materials, in step (1), the mixing is performed by grinding, and preferably the grinding time is more than 10 minutes, for example, 10-30 minutes.
[0059] According to a preferred embodiment of the present invention, the material mixture does not contain a solvent. The solvent includes but is not limited to acetonitrile (ACN), N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), tetrahydrofuran (THF), etc. In other words, the solid electrolyte membrane of the present invention is prepared by a dry process.
[0060] In step (2), the uniformly mixed material mixture is prepared to form a composite electrolyte membrane. For example, the molding can be performed by pressure molding. Preferably, the molding temperature is 40-90° C., more preferably 60-80° C. The pressure molding can be performed by flat plate pressing or roller pressing, using any instrument commonly used in the art for pressing composite electrolyte membranes.
[0061] According to a preferred embodiment of the present invention, in step (2), before the molding, the material mixture is subjected to one or more of the following treatments: fiberization, melting, and softening. Fiberization may include applying a certain shear force to the material mixture to fiberize it; melting may include heating the material mixture to a temperature above the melting point of the polymer to melt it; and softening may include heating the material mixture to a temperature slightly lower than the melting point of the polymer to soften it.
[0062] The third aspect of the present invention provides the use of the composite electrolyte membrane of the first aspect or the composite electrolyte membrane prepared by the preparation method of the second aspect in a lithium ion battery.
[0063] Example
[0064] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0065] In the following examples and comparative examples, the relevant reagents used are shown in Table 1 below.
[0066] Table 1
[0067]
[0068] In the following examples and comparative examples, the main instruments used are as follows:
[0069] High speed grinder: Liren grinding mill, Liren Electric, MFJ-W317.
[0070] Roller press: Laboratory heated pole piece roller press, Xiamen Tianmeifu Machinery Equipment Co., Ltd., TMAX-JRDG100.
[0071] Example 1
[0072] 8 g of LLZO powder with a particle size of 500 nm, 0.2 g of PEO, 0.4 g of polyether polyurethane, 0.6 g of LiTFSI and 0.8 g of SN were weighed and ground for 30 min. The ground electrolyte mixture was repeatedly rolled on a roller press at 80° C. to form a composite electrolyte membrane with a thickness of 30 μm.
[0073] Example 2
[0074] A composite electrolyte membrane was prepared according to the method in Example 1, except that the added amount of PEO was changed to 0.3 g and the added amount of polyether polyurethane was changed to 0.3 g.
[0075] Example 3
[0076] A composite electrolyte membrane was prepared according to the method in Example 1, except that the amount of PEO added was changed to 0.4 g and the amount of polyether polyurethane added was changed to 0.2 g.
[0077] Example 4
[0078] A composite electrolyte membrane was prepared according to the method in Example 1, except that the amount of LLZO powder added was changed to 6 g.
[0079] Example 5
[0080] A composite electrolyte membrane was prepared according to the method in Example 1, except that the amount of LLZO powder added was changed to 9 g.
[0081] Comparative Example 1
[0082] A composite electrolyte membrane was prepared according to the method in Example 1, except that the amount of PEO added was changed to 0.6 g and polyether polyurethane was not added.
[0083] Comparative Example 2
[0084] A composite electrolyte membrane was prepared according to the method in Example 1, except that the amount of polyether polyurethane added was changed to 0.6 g and PEO was not added.
[0085] Comparative Example 3
[0086] The composite electrolyte membrane was prepared by a wet method. Specifically, 0.3 g PEO and 0.3 g polyether polyurethane were added to the ACN solvent and stirred to fully dissolve. 8 g 500 nm LLZO powder, 0.6 g LiTFSI and 0.8 g SN were added to the mixed solution in sequence, stirred, and ultrasonicated to make the slurry evenly dispersed. The slurry was cast on a PET film and thoroughly dried at 60 ° C. A composite electrolyte membrane with a thickness of 30 μm was obtained.
[0087] Test Case
[0088] The composite electrolyte membranes obtained in the above examples and comparative examples were subjected to performance tests according to the following method.
[0089] Test method:
[0090] Ionic conductivity: Stainless steel sheets were placed on both sides of the solid electrolyte membrane as blocking electrodes, button cells were assembled, and AC impedance tests were performed using an electrochemical workstation. Appropriate amplitude voltage and frequency were set, and the test results were fitted and calculated to obtain the ionic conductivity.
[0091] The formula for calculating ionic conductivity is: σ = d / (R × S), where σ represents conductivity; R is the impedance value of the electrolyte membrane obtained by the test, in Ω; S is the electrode area, in cm 2 ; d is the thickness of the electrolyte membrane, in cm.
[0092] Tensile strength refers to the ratio of the maximum tensile force to the cross-section of the sample during the tensile test. The tensile strength and elongation are measured according to the determination method for plastic films GB / T1040.3 2006.
[0093] The measured results are shown in Table 2.
[0094] Table 2
[0095] <![CDATA[Ionic conductivity (10 -4 S / cm)]]> Tensile strength(MPa) Elongation(%) Example 1 2.18 5.5 20 Example 2 5.62 6.2 25 Example 3 4.03 2.8 12 Example 4 3.85 2.6 11 Example 5 2.91 2.1 5 Comparative Example 1 0.71 0.9 8 Comparative Example 2 0.55 5.8 23 Comparative Example 3 0.42 0.3 1
[0096] It can be seen from the results in Table 1 that, compared with Comparative Examples 1-3, the embodiments of the present invention can provide a composite electrolyte membrane having both high ionic conductivity and high mechanical strength, flexibility and ductility. Moreover, when the content of PEO is 80% and the weight ratio of PEO to polyether polyurethane is 1:1, the ionic conductivity and tensile strength of the obtained composite electrolyte membrane are the highest.
Claims
1. A composite electrolyte membrane, characterized in that: The composite electrolyte membrane comprises an oxide electrolyte, polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer; Wherein, relative to the total weight of the composite electrolyte membrane, the oxide electrolyte accounts for more than 50%.
2. The composite electrolyte membrane according to claim 1, wherein: Relative to the total weight of the composite electrolyte membrane, the oxide electrolyte accounts for 50-90%, the polyethylene oxide accounts for 1-10%, the polyether polyurethane accounts for 1-10%, the lithium salt accounts for 1-15%, and the plasticizer accounts for 1-15%; Preferably, the ionic conductivity of the composite electrolyte membrane is 2*10 -4 S / cm or more, preferably 3*10 -4 S / cm or more.
3. The composite electrolyte membrane according to claim 1 or 2, wherein: The oxide electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP); Preferably, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB); Preferably, the plasticizer is one or more of succinonitrile, polyethylene glycol, and dioctyl phthalate.
4. The composite electrolyte membrane according to any one of claims 1 to 3, wherein: The weight ratio of the polyethylene oxide to the polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.
2.
5. The composite electrolyte membrane according to any one of claims 1 to 4, wherein: The composite electrolyte membrane is prepared by a dry method.
6. A method for preparing a solid electrolyte membrane, characterized in that: The preparation method comprises the following steps: (1) mixing an oxide electrolyte with polyethylene oxide, polyether polyurethane, a lithium salt and a plasticizer to obtain a material mixture; (2) forming the material mixture to obtain a solid electrolyte membrane; Wherein, relative to the total weight of the material mixture, the oxide electrolyte accounts for more than 50%.
7. The preparation method according to claim 6, wherein: Relative to the total weight of the material mixture, the oxide electrolyte accounts for 50-90%, the polyethylene oxide accounts for 1-10%, the polyether polyurethane accounts for 1-10%, the lithium salt accounts for 1-15%, and the plasticizer accounts for 1-15%; Preferably, the material mixture does not contain a solvent.
8. The preparation method according to claim 6 or 7, wherein: The oxide electrolyte is one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum titanium oxide (LLTO), and lithium aluminum germanium phosphate (LAGP); Preferably, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalatoborate (LiDFOB); Preferably, the plasticizer is one or more of succinonitrile, polyethylene glycol, and dioctyl phthalate; Preferably, the weight ratio of the polyethylene oxide to the polyether polyurethane is 1:0.5-2, preferably 1:0.8-1.
2.
9. The preparation method according to any one of claims 6 to 8, wherein In step (1), the mixing is performed by grinding, and preferably the grinding time is more than 10 minutes; Preferably, in step (2), the molding is performed by pressure molding, and the molding temperature is preferably 60-80°C; Preferably, in step (2), before the molding, the material mixture is subjected to one or more of the following treatments: fiberization, melting, and softening.
10. Use of the composite electrolyte membrane according to any one of claims 1 to 5 or the composite electrolyte membrane prepared by the preparation method according to any one of claims 6 to 9 in a lithium ion battery.